Emotions shape memory suppression in trait anxiety - Marzi, Tessa; Regina, Antonio; Righi, Stefania (Frontiers in Psychology, 2014)
The question that motivated this study was to investigate the relation between trait anxiety, emotions and memory control. To this aim, memory suppression was explored in high and low trait anxiety individuals with the Think/No-think paradigm. After learning associations between neutral words and emotional scenes (negative, positive, and neutral), participants were shown a word and were requested either to think about the associated scene or to block it out from mind. Finally, in a test phase, participants were again shown each word and asked to recall the paired scene. The results show that memory control is influenced by high trait anxiety and emotions. Low trait anxiety individuals showed a memory suppression effect, whereas there was a lack of memory suppression in high trait anxious individuals, especially for emotionally negative scenes. Thus, we suggest that individuals with anxiety may have difficulty exerting cognitive control over memories with a negative valence. These findings provide evidence that memory suppression can be impaired by anxiety thus highlighting the crucial relation between cognitive control, emotions, and individual differences in regulating emotions.